Obtenção e propriedades de compósitos particulados e laminados do sistema magnetoelétrico livre de chumbo 0,94(Na₀‚₅Bi₀‚₅)TiO₃-0,06BaTiO₃/CoFe₂O₄ - Silva, Gislayne Rayane Alves da (2024)
Multifunctional materials comprising ferroelectric and ferrimagnetic heterostructures, designated as magnetoelectric multiferroic composites, exhibit characteristics associated with both ferroic orderings. The coupling between the ferroic orderings in these materials is extrinsic and is mainly susceptible to factors such as synthesis, processing, connectivity, and the physical properties of the constituent phases. Consequently, the development of these materials presents a significant challenge in terms of achieving adequate homogeneity between the phases that comprise them. Different connectivities, including 0-3 (particulates) and 2-2 (laminates), are investigated to enhance the magnetoelectric coupling between these phases. Furthermore, chemical synthesis and non-traditional sintering techniques have been employed to produce composites with good magnetoelectric performance. The objective of this research was to develop lead-free particulate and laminated magnetoelectric composites from the 0.94(Na0.5Bi0.5)TiO3-0.06BaTiO3/CoFe2O4 (NBT-BT6/CFO) system using synthesis and sintering methods that provide homogeneity between the constituent phases, as well as correlating the methods used to obtain them with the physical performance of the materials developed. The particulate composites were, originally, co-synthesized in different compositions using the polymeric precursor synthesis method, promoting the crystallization of the NBT-BT6 and CFO phases in a single heat treatment cycle at 750 °C for one hour, resulting in the formation of nanometric powders with good homogeneity of distribution between the phases. Subsequent conventional and microwave-assisted sintering resulted in the effective densification of the bulk. The laminated composites were obtained from nanopowders synthesized from the constituent phases in different configurations of the NBT-BT6/CFO system. This was achieved by employing co-sintering and the hot pressing method, which represents a novel approach for this system. The dielectric, piezoelectric, and magnetoelectric behaviors were evaluated and correlated with their respective connectivity, where the composition containing 20% CFO stood out among the particulates and the laminates, the configuration with 2 layers of CFO and 1 of NBT-BT6 showed the best performance in terms of magnetoelectric response.